Minimally invasive cytoreductive surgery in advanced ovarian cancer: A nonselected consecutive series of robotic-assisted cases - Shammas, Natalie; Avila, Rosa; Khatchadourian, Christopher; Spencer-Smith, Erland Laurence; Stern, Lisa; Vasilev, Steven (Clinical Journal of Obstetrics and Gynecology, 2023)
The gold standard for advanced-stage ovarian cancer surgery entails exploration via a midline vertical laparotomy. Studies have shown that minimally invasive surgery (MIS) can be a safe and effective method for the surgical management of early ovarian cancer. In some cases, MIS can also be selectively used for cytoreductive surgery in cases with advanced-stage ovarian cancer. The robotic platform has the potential to provide similar outcomes to the laparotomy-based standard of care in advanced complex surgery while accelerating recovery, minimizing morbidity, and reducing perioperative complications. The primary objective of this study was to evaluate surgical and perioperative outcomes in patients with advanced ovarian carcinoma who underwent robotic-assisted cytoreduction. A chart review of a nonselected consecutive series of all patients undergoing surgical management of advanced ovarian cancer between 7/1/2017 and 12/31/2021 was conducted. All patients that were diagnosed with Stage III to IV ovarian cancer between the timeframe underwent robotic-assisted cytoreductive surgery at two urban community teaching hospitals in Los Angeles. Twenty-five patients were identified and included in this study. All surgeries were performed by a single surgeon. Optimal or complete CRS was achieved in 96% of the patients (24 of 25 cases). Seven (28%) underwent primary cytoreduction (PCRS) and 18 (72%) underwent interval cytoreduction (ICRS). The estimated median blood loss was 100 mL (25-500 mL), the median operative time was 5.9 hours (3.1-10.5 hours), and the conversion rate to open laparotomy was 0%. There were no intraoperative complications and the readmission rate within 30 days was 4% (1 patient) for ileus, which was managed conservatively. Currently, 64% of the patients in the case series remain alive. The median survival has not been reached. The median follow-up is 4.08 years. Results presented from this nonselected, consecutive case series illustrate how a minimally invasive robotic approach can be safely used in place of the standard exploratory laparotomy for ovarian cytoreduction.